Modeling mixed mode cracking in concrete through a regularized extended finite element formulation considering aggregate interlock. (December 2021) - Benvenuti, E.; Orlando, N.
Abstract: Mixed mode cracking in concrete keeps being a challenging issue in computational fracture mechanics. While uncracked concrete develops cracks perpendicular to the direction of the maximum principal tensile stress, the crack edges will expectedly open, mutually slide, and transmit both normal and shearing stresses. In the present formulation, we replace the damage band with a regularized strain band by enriching the space of the approximating functions in compliance with the regularized extended finite element model developed by the authors. Our clue is that a discriminant factor to choose the appropriate expression of the regularized strain relies upon the concept of stress compatibility modified to consider aggregate interlock. In particular, we resort to a simplified phenomenological saw-tooth model of the crack surface asperities. We show the capability of the methodology to capture both structural behavior and crack paths in a set of bending tests carried out on concrete specimens. Though phenomenological, the resulting approach is novel, conceptually simple and reliable for it directly reproduces the expected kinematics and structural results. Highlights: The localized strain is modeled through the regularized XFEM. Stress compatibility and aggregate interlock are considered. A saw-tooth model of the crack surface asperities is used. The regularization length is linked with the width of the FPZ. Both structural results and crack paths are captured.